Agricultural Value Chain - Egilmez, Gokhan (IntechOpen, 2018)
This book covers the agricultural value chain issues that occur in different parts of the world and aims to increase our understanding about the sustainable agricultural value chain paradigm. By reading through these chapters, the readers will witness various interesting, sometimes sad, commonalities among different regions of the world, where smallholder farmers and producers are severely affected by various agricultural policy deficiencies or mistakes and inexistences. The book consists of 14 chapters, which comprehensively cover over 20 agricultural products from more than 15 different regions of the world. Various qualitative and quantitative research methods are presented including surveys, case studies, interviews, price transmission, risk analysis, and multiagent system technology.